An evaluation of adult literacy campaigns in Turkey - Kirazoğlu, Cem. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2003., 2003)
The aim of this study is to make an evaluation of adult literacy campaigns conducted in Turkey since the establishment of the Turkish Republic until 1980's, in order to analyze their approaches and philosophies, and evaluate them with a Freirean viewpoint. For this purpose, the first literacy campaign in 1928 conducted after the transition into the Latin alphabet, and the second literacy campaign in 1981 conducted after the 1980 Military Coup was taken into consideration. Other large-scale literacy activities conducted by the state agencies in 1958, 1962, and 1972 were not taken into consideration for the analysis since these activities were oriented toward a definite segment of the society. The concept of campaign in this study was defined as an official activity, the target of which is the whole population in a country rather than a definite segment of the society.As a result of this analysis, adult literacy campaigns conducted in Turkey are found to have basic, traditional, and functional approaches. The aim of the first literacy campaign is different than that of the second campaign. The first literacy campaign was one of the tools of the establishment of the nation state, which needed a new type of citizen who was equipped with the skills of reading and writing with the Latin alphabet. It was argued that the real impetus behind this project was the adaptation into the new economic, cultural and political system. On the other hand, the aim of the second literacy campaign conducted after 1980 Military Coup is to provide the contribution of the adult illiterates to the economic growth, industrial development, and technological improvement the Turkish Republic had to fulfill. Both of the campaigns are not successful in reaching all of the illiterate population. Thus, the number of the illiterates have increased. But one point that has to be addressed is the fact that the first literacy campaign was conducted with a higher enthusiasm and motivation, and the interest of the adult illiterates could be attracted.Looking from a Freirean approach, the reason why both campaigns have been unsuccessful in a sense of not reaching all of the population, and not attracting the interest of all segments of the society is that they have not considered the needs and expectancies of all of the population. As the date of the first campaign preceded the rise of the Freirean approach the implementation of that approach could not be expected. However, the needs and expectancies of the illiterate population could be investigated more effectively, which would have create a basis for further campaigns and activities. In the second campaign, the Freirean approach could be implemented after a deeper investigation of its implementation throughout the world. The most important reason why this approach was not implemented in the second campaign is that this campaign having only one type of curriculum was conducted with an offcial centralist understanding. However, the Freirean approach is one that the needs and expectancies of the adult illiterate have primary importance, and the curriculum takes a form in the direction of these needs and expectancies. This approach intends to develop the awareness of adults to situate themselves into the realities of the world and help them ask critical questions about their life.
Keywords: Literacy programs.; Adult education -- Turkey -- Evaluation.; Educational evaluation -- Developing countries.; Literacy programs -- Developing countries -- Evaluation.